2014
DOI: 10.4238/2014.july.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-149C>T and miR-499A>G polymorphisms with the risk of hepatocellular carcinoma in the Chinese population

Abstract: ABSTRACT. We investigate the potential association of miR-149C>T and miR-499A>G polymorphisms and the risk of hepatocellular carcinoma (HCC). A matched case-control study of 152 cases and 304 controls were conducted. The miR-149C>T and miR-499A>G genotypes were analyzed using duplex polymerase chain reaction with restricted fragment length polymorphism. HCC patients were more likely to be smokers and drinkers, have hepatitis B and C virus infections, and a family history of cancer. The miR-149 CC genotype was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…As for this research, ANRIL showed a negative association with miR-499a, and PDCD4 was a target of miR-499a. miR-499a polymorphism was associated with the progression of several cancers, such as oral squamous cell carcinoma [39], breast cancer [40] and hepatocellular carcinoma [41]. The genetic polymorphism of miR-499 A>G (rs3746444) is also associated with the risk of ischemic stroke in a Chinese people [42].…”
Section: Discussionmentioning
confidence: 99%
“…As for this research, ANRIL showed a negative association with miR-499a, and PDCD4 was a target of miR-499a. miR-499a polymorphism was associated with the progression of several cancers, such as oral squamous cell carcinoma [39], breast cancer [40] and hepatocellular carcinoma [41]. The genetic polymorphism of miR-499 A>G (rs3746444) is also associated with the risk of ischemic stroke in a Chinese people [42].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ADH7 expression levels gradually increased with an increase in patient age, while CYP26B1 expression gradually declined with a decrease in patient age, indicating that ADH7 and CYP26B1 are correlated with the differential progression of cervical cancer between different age groups. It has been revealed that miR-499a influences the tumorigenesis of several different types of cancer, including breast cancer (43) and hepatocellular carcinoma (44). In addition, miR-499a contributes to the migration and proliferation of hepatitis B virus-associated hepatocellular carcinoma (HCC) cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have focused on the SNPs in miRNAs and have investigated their potential role in HCC susceptibility [10, 11, 14-28]. A deeper understanding of the association between these polymorphisms and HCC would help early detection and prevention of this deadly disease in high-risk populations such as the Chinese.…”
Section: Discussionmentioning
confidence: 99%